2007
DOI: 10.1108/09513540710780000
|View full text |Cite
|
Sign up to set email alerts
|

International students' motivations for studying in UK HE

Abstract: PurposeInternational students' HE decision making is a high stakes process. There is an insufficient evidence base that would aid university level strategic planning in areas of recruitment from the African continent and in supporting its students to maximise the benefits from a UK HE experience. This paper aims to explore the decision making and experience of African students in UK HE and provides hypothesis for re‐conceptualising these processes.Design/methodology/approachThe research was exploratory and par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
95
0
15

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 196 publications
(114 citation statements)
references
References 17 publications
4
95
0
15
Order By: Relevance
“…Students evaluate programmes on the following criteria: programme offerings (Nagaraj et al, 2008), quality (Hassan & Sheriff, 2006), content and structure (Wagner & Fard, 2009;Joseph & Joseph, 2000) and international recognition (Maringe & Carter, 2007). Besides that, the programme's degree conferred by Malaysia's private HEI is likely to be recognized in the respective foreign students' country when it is accreditated by the Malaysian Qualification Agency (MQA).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Students evaluate programmes on the following criteria: programme offerings (Nagaraj et al, 2008), quality (Hassan & Sheriff, 2006), content and structure (Wagner & Fard, 2009;Joseph & Joseph, 2000) and international recognition (Maringe & Carter, 2007). Besides that, the programme's degree conferred by Malaysia's private HEI is likely to be recognized in the respective foreign students' country when it is accreditated by the Malaysian Qualification Agency (MQA).…”
Section: Literature Reviewmentioning
confidence: 99%
“…The cost of going to university plays an influential role when selecting between several universities that offer a similar course (Price and Matzdorf, 2003). However, Maringe and Carter (2007) in the study on international students' motivation to pursue higher education in UK showed a negative relationship between cost and student enrolment, meaning cost did not have an impact on other students. They further highlighted that most students come from wealthy families and they could afford any university fees despite the demand of the institution alone.…”
Section: Impact Of Costmentioning
confidence: 95%
“…An established literature exists on the motivation of students to study overseas, and in the choice of country and institution (e.g., Maringe and Carter, 2007). This includes the theorization and modelling of decision-making processes, none of which factor in partners and/or children (Mazzarol and Soutar, 2002;Cubillo et al, 2006;Altbach and Knight, 2007).…”
Section: Visibility Of Students' Familiesmentioning
confidence: 99%